A Model for Malpractice Preparedness for Plastic Surgery Residents - Simran K. Chandawarkar, BS; Neal R. Reisman, MD, JD, FACS; Jeffrey E. Janis, MD, FACS (Plastic and Reconstructive Surgery, Global Open, 2025)
Background:. Plastic surgery has the fifth largest number of malpractice claims among all specialties. In 2023 alone, 73% of plastic surgeons across several states reported being involved in a medical malpractice case. Lawsuits are costly and disrupt physicians’ personal and professional lives for years. Despite this, plastic surgeons are underprepared to face lawsuits, and most learn as they go. We aim to identify basic medicolegal tenets that plastic surgeons must know and propose a training model for residents. Methods:. PubMed, Cochrane, Web of Science, and National Practitioner Data Bank databases were searched using relevant keywords related to plastic surgery and malpractice/medicolegal education. Relevant literature on medicolegal education was screened. Guidelines from surgical professional organizations were reviewed alongside internet sources. Using these materials, a comprehensive educational summary of relevant medicolegal principles was compiled. Results:. Barely 3 of the 219 articles identified directly addressed malpractice education in plastic surgery—and none offered clear guidelines. Nonmedical sources such as YouTube provided more descriptive insight than many professional organizations. Some case-based modules were identified for general surgical trainees, but they were not useable for plastic surgery. An educational module is proposed to guide residents through each phase of a lawsuit, help them identify key strategic mitigation measures, and understand settlement options in simple terms that a clinician can easily understand. Relevant risk-mitigation strategies to avoid lawsuits via practical “pain-point case scripts” are included. Conclusions:. Medicolegal education is essential to prepare plastic surgeons for clinical practice. Integrating this in their curriculum will bridge the current gap.